Strategi Tim Sukses Pemenangan Askolani-Slamet Dalam Pemilihan Bupati Banyuasin Tahun 2018 - Wulandari, Indah; Kariem, Muhammad Qur’anul; Amaliatulwalidain, Amaliatulwalidain (Jurnal Publisitas, 2022)
Political marketing strategy is one of the factors that support the victory of a candidate in an election. In 2018, there was an interesting phenomenon in the Pilbub Banyuasin. Where the votes from the Askolani-Slamet pair were categorized as getting quite a large number of votes among the other 5 candidates. Seeing this condition, researchers are interested in conducting research to find out the strategy and significance of the Askolani-Slamet success team in the Banyuasin Pilbub. This study uses descriptive qualitative methods, where data collection techniques use interviews, documentation and observation. The results of this study stated that the factor of the victory of the Askolani-Slamet coalition in the Regional Head General Election in Banyuasin Regency in 2018 was influenced by three factors; First, there is a coalition of political parties. Second, there is political participation and involvement of the Banyuasin community in granting voting rights in the 2018 post-conflict local election. Third, there are modalities, which consist of political capital, social capital, cultural capital and economic capital. Political marketing that has been carried out is the formation of figures and complex campaign programs that include 4 indicators that use Niffenger's theory in the book Firmanzah: 2020 that runs optimally and runs well, namely determining political products, promotions, prices, and places.